Lung Function Parameters in Patients with Dilated Cardiomyopathy Complicated by Pulmonary Hypertension - T. A. Abdullaev; Ya. R. Ahmatov; B. U. Mardanov; R. Sh. Bekbulatova (Столичная издательская компания, 2016)
Aim. To study clinical and morphofunctional indicators of respiratory function in patients with dilated cardiomyopathy (DCM) with and without pulmonary hypertension (PH).Material and methods. 91 patients with idiopathic DCM (34 women and 57 men; mean age of 46.4±13.7 years) were included into the study. 25 (27.4%) patients had right ventricular DCM (RV DCM). 6-minute walking test (6MWT), the standard 12-lead ECG, spirography, echocardiography were performed in all patients. PH occurred in 48 of DCM patients (Group I) and 43 DCM patients had no PH (Group II). A number of patients with RV DCM in Groups I and II was 11 (23%) and 14 (32.5%), respectively.Results. Pulmonary artery systolic pressure (PASP) in group I was 48.1±10.7 mmHg (in 71% of the patients - degree 1 of PH, and in 29% - degree 2). A significant decrease in the majority of speed indicators of respiratory functions was found in Group I. The inverse relationship between PASP and Tiffno index (p=0.03) and a positive correlation between forced vital capacity (53.17±9.21%) and 6MWT distance (206.7±80.3 m; p=0.017) were found in patients of Group I.Conclusion. PH syndrome often aggravates the DCM course. Forced expiratory volume in the first second, Tiffno index, and some speed indicators show disorders of respiratory function in DCM patients.